USURY LAWS IN JUDAISM; A CRITICAL STUDY - Amira Sami; Dr. Sami Ul Haq; Naila Mushtaq; Tanveela Tahira; Dr. Hafsah Ayaz (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The notion of usury in Judaism is critically examined in this article with an emphasis on its historical evolution, interpretation, and current applicability. Within Jewish religious and societal contexts, usury (the charging of excessive interest on loans) has long been a topic of ethical and legal discussion. This study covers the development of Jewish usury laws and their guiding principles through an examination of ancient texts, rabbinical commentaries, and legal decisions. The research starts by examining the history of usury laws in Jewish scripture, particularly in the Talmud and the Hebrew Bible. To understand the underlying motives and societal issues that affected the formation of Jewish usury regulations, it analyses passages that speak to loan practices and their moral ramifications. The biblical prohibition receives special consideration. The biblical prohibition against charging interest to fellow Jews is given special consideration since it has important ramifications for societal harmony and economic justice. Jewish usury regulations add to the larger conversation on ethical finance and the interaction of economic principles and religious beliefs. Policymakers, academics, and practitioners can learn important insights into the Jewish perspective on lending, borrowing, and economic justice by comprehending the historical development and guiding principles of usury regulations. This will promote communication and understanding between various communities.